2018
DOI: 10.2478/helm-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, abundance and intensity of eggs and oocysts of gastrointestinal parasites in the opossum Didelphis virginiana Kerr, 1792 in Yucatan, Mexico

Abstract: SummaryVirginia opossum, Didelphis virginiana, is a synanthropic mammal associated with peridomestic areas of Yucatán, However, little is known about the gastrointestinal parasite infections of this species. The infection prevalence, mean abundance and mean intensity of eggs and oocysts of gastrointestinal parasites, in opossums captured in the peridomestic areas were estimated in six rural localities of Yucatán, Mexico. Eighty-four faecal samples were processed by flotation technique. McMaster test was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The opossum is a generalist species that can be found in a variety of different habitats in the neo-tropics [ 48 ]. The opossum is often described as a synanthrope, as it is frequently sighted near human dwellings in the region [ 1 , 49 ]. The omnivorous diet of this species is described as wide, diverse, and opportunistic, ranging from fruits to small animals to fecal matter [ 50 , 51 ].…”
Section: Occurrence In Didelphis Sppmentioning
confidence: 99%
See 4 more Smart Citations
“…The opossum is a generalist species that can be found in a variety of different habitats in the neo-tropics [ 48 ]. The opossum is often described as a synanthrope, as it is frequently sighted near human dwellings in the region [ 1 , 49 ]. The omnivorous diet of this species is described as wide, diverse, and opportunistic, ranging from fruits to small animals to fecal matter [ 50 , 51 ].…”
Section: Occurrence In Didelphis Sppmentioning
confidence: 99%
“…Many studies have identified this species as a host or reservoir vector species for a plethora of endoparasites and infectious agents that can cause disease [ 1 , 49 , 52 , 53 ], including the two protozoan species Cryptosporidium and Giardia , which have both been reported in Didelphis opossums D. albiventris [ 7 ], D. virginiana [ 54 ], and D. aurita [ 1 ]. The opossums’ ability to act as a host for these two infectious parasites, combined with its varied diet and synanthropic behavior, make it a likely candidate for the spread of zoonotic parasites.…”
Section: Occurrence In Didelphis Sppmentioning
confidence: 99%
See 3 more Smart Citations